Insulin Resistance and Glucose Dysregulation in HIV Treated Patients - Yancheng, Prof. Xu; A. ALI, Salama; Xiaoqi, Ass. Prof Chen (International Journal of Scientific Research and Management (IJSRM), 2018)
The emergence of a new HIV infected elderly population as a result of chronic use of highly active antiretroviral therapy (HAART) has attributed to the increase of metabolic disorders particularly insulin resistance(IR) and diabetes, dyslipidemia and lipodystrophy.The pathogenesis of these metabolic derangements is complex and multifactorial and could be a consequence of an interplay between traditional age-related risk factors, HIV infection, antiretroviral therapy effects, the inflammatory effect and immune activation in this population. IR in HIV infection has numerous causes which include not only the direct effects of antiretroviral drugs but also factors such as aging and restoration to health accompanied by fat accumulation. Studies have shown that insulin levels increase over time with antiretroviral therapy, likely the result of improved health, fat accumulation, and aging, and that increases in visceral fat and upper trunk fat are associated with a higher risk of IR in HIV infected and uninfected individuals. Since metabolic and cardiovascular disease (CVD) increase with aging, knowledge of the optimal management of these conditions is essential for practitioners caring for HIV infected patients including endocrine subspecialists. This review aims to synthesize the current knowledge on insulin resistance and dysregulation of glucose on treated HIV population